Glucose Sensors: 2D Colloidal Array of Glucose‐Conjugative Conductive Microparticles for a Pressure‐Mediated Chemiresistive Sensor Platform (Adv. Funct. Mater. 35/2020). (26th August 2020) - Choi, Song‐Ee; Park, Daehwan; Hwang, Hyejin; Seo, Minjeong; Lee, Duho; Jeong, Unyong; Kim, Jin Woong
Abstract : In article number 2000431, Unyong Jeong, Jin Woong Kim, and co‐workers report a chemiresisitive sensor technology. Taking advantage of the pressure‐responsive resistance change in sensor microparticles induced by a specific conjugation reaction of glucose, they show that this glucose sensor is able to detect a wide range of glucose concentrations with high sensitivity and selectivity, thus exhibiting significant potential for the development of non‐invasive glucose sensors.